2012
DOI: 10.1002/mnfr.201200085
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein and fat play different roles in affecting the bioavailability and the antioxidant activity of jujube juice phenolics in rats

Abstract: The present study suggests that when ingested with jujube juice, milk proteins and fat play different roles in affecting the bioavailability and the antioxidant activity of jujube juice phenolics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Different food components (dairy protein and jujube juice) improve antioxidant and health benefits beyond those arising from individual components. This complex was thus proved a potent antioxidant in biological systems (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Different food components (dairy protein and jujube juice) improve antioxidant and health benefits beyond those arising from individual components. This complex was thus proved a potent antioxidant in biological systems (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Lesser, Cermak, and Wolfram (2004), oil addition to diet increased the bioavailability of quercetin and it was related to the delay in absorption and metabolism of oily foods that resulted in more quercetin absorption. Zhang et al (2012) also found that milk fat did not interact with jujube juice phenolics. However, when jujube juice was ingested with whole milk, a significant reduction in the bioavailability of phenolics was reported and was related to the formation of complexes between proteins, fats, and phenolics during digestion.…”
Section: Changes In Total Phenolic Contents After Codigesting Pomegramentioning
confidence: 90%
“…However, when jujube juice was ingested with whole milk, a significant reduction in the bioavailability of phenolics was reported and was related to the formation of complexes between proteins, fats, and phenolics during digestion. Some in vivo studies are available on the effect of oil or fats on the bioavailability of phenolic compounds (Lesser et al, 2004;Mullen et al, 2008;Zhang et al, 2012) but in vitro studies are very few (Ortega et al, 2009). …”
Section: Changes In Total Phenolic Contents After Codigesting Pomegramentioning
confidence: 99%
“…Zhang et al . () evaluated the effects of skimmed milk, milk fat and whole milk on the bioavailability of phenols and the plasma antioxidant capacity of rats. It was concluded that milk fat alone did not interact with jujube juice polyphenols.…”
Section: Polyphenols: Synthesis Classification and Consequences In Vmentioning
confidence: 99%